2020
DOI: 10.3390/cells9030601
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in Multiple Myeloma

Abstract: Multiple myeloma is a complex disease and immune dysfunction has been known to play an important role in the disease pathogenesis, progression, and drug resistance. Recent efforts in drug development have been focused on immunotherapies to modify the MM disease process. Here, we summarize the emerging immunotherapies in the MM treatment landscape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 227 publications
0
39
0
Order By: Relevance
“…Indeed, it has been shown that the anti-CD38 mAb Daratumumab enhances effectors cell-mediated lysis, degranulation, and ADCC against CD38 + tumor cells [ 84 , 85 , 86 , 87 ] improving the overall response rate in MM patients [ 88 , 89 , 90 , 91 ]. Interestingly, the efficacy of Daratumumab can be enhanced when combined with drugs or other mAbs [ 85 , 90 , 92 ]. Other anti-CD38 mAbs under investigation in hematological malignancies are Isatuximab and MOR-202 [ 93 , 94 , 95 ].…”
Section: Current Advanced Therapy In Hematological Malignanciesmentioning
confidence: 99%
“…Indeed, it has been shown that the anti-CD38 mAb Daratumumab enhances effectors cell-mediated lysis, degranulation, and ADCC against CD38 + tumor cells [ 84 , 85 , 86 , 87 ] improving the overall response rate in MM patients [ 88 , 89 , 90 , 91 ]. Interestingly, the efficacy of Daratumumab can be enhanced when combined with drugs or other mAbs [ 85 , 90 , 92 ]. Other anti-CD38 mAbs under investigation in hematological malignancies are Isatuximab and MOR-202 [ 93 , 94 , 95 ].…”
Section: Current Advanced Therapy In Hematological Malignanciesmentioning
confidence: 99%
“…In addition, other immunotherapies that are showing promise in multiple myeloma clinical trials will hopefully be offered to patients with AL amyloidosis, including chimeric antigen receptor T cells, bispecific T-cell engager antibodies, and antibody–drug conjugates. 68
Fig. 2 Improved survival over time: overall survival (OS) for AL amyloidosis by period of diagnosis.
…”
Section: Novel Therapies For Light Chain Amyloidosismentioning
confidence: 99%
“…Multiple myeloma (MM) remains an incurable haematological malignancy although substantial progress in the treatment has occurred in recent years (1). The introduction of immunomodulatory drugs (IMiDs) such as thalidomide, lenalidomide, and pomalidomide has resulted in significant improvements for the long-term survival and the quality of life of MM patients (2,3). The other drugs, namely proteasome inhibitors (bortezomib, carfilzomib, ixazomib), immune checkpoint inhibitors, and monoclonal antibodies have contributed substantially to improve the prognosis of MM patients (2,4).…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of immunomodulatory drugs (IMiDs) such as thalidomide, lenalidomide, and pomalidomide has resulted in significant improvements for the long-term survival and the quality of life of MM patients (2,3). The other drugs, namely proteasome inhibitors (bortezomib, carfilzomib, ixazomib), immune checkpoint inhibitors, and monoclonal antibodies have contributed substantially to improve the prognosis of MM patients (2,4). Apart from these agents, another way of treatment is autologous stem-cell transplantation (ASCT), which is prescribed for patient populations with limited comorbidities and in good overall condition (5).…”
Section: Introductionmentioning
confidence: 99%